1973
DOI: 10.1177/002221947300600410
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Revised and Experimental Editions of the Illinois Test of Psycholinguistic Abilities

Abstract: Selected subtests of the experimental and revised editions of the Illinois Test of Psycholinguistic Abilities were administered to 30 six-year-old subjects. Correlations between subtests of the two editions were found to be of the same general magnitude as test-retest coefficients reported for the subtests of each edition. It appears that performance on one edition of the ITPA may be compared with performance on the other, and that the two editions may be used interchangeably for some purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1974
1974
1982
1982

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Several studies reported only subtest data which were combined to form a total score for analysis purposes. No distinction was made between the 1961 and 1968 editions of the ITPA since they have been found to be interchangeable (Waugh, 1973).…”
Section: Data Collectionmentioning
confidence: 99%
“…Several studies reported only subtest data which were combined to form a total score for analysis purposes. No distinction was made between the 1961 and 1968 editions of the ITPA since they have been found to be interchangeable (Waugh, 1973).…”
Section: Data Collectionmentioning
confidence: 99%